ANALISIS PEMANDU WISATA SEBAGAI MEDIA PROMOSI DI MANDALIKA, NUSA TENGGARA BARAT - Debi Rusmiati; Doddy Wihardi (Media Bina Ilmiah, 2025)
The Mandalika Special Economic Zone (KEK) is one of 10 new Balis which is a government program to introduce Indonesian tourism to the world. Mandalika offers a combination of natural tourism, culture and new advantages such as the Mandalika Circuit which is increasingly attracting the attention of domestic and foreign tourists. Along with the growth of the tourism sector, an effective promotional strategy is very important considering the increasingly tight competition between similar destinations. One of the key elements in a tourism promotion strategy is the role of tour guides. Tour guides not only function as conveyors of information about tourist attractions, but also introduce local culture and in-depth experiences for tourists. Although the potential of tour guides in Mandalika is very large, research on the role of tour guides in promotion is still limited. Therefore, this study is important to explore how tour guides can be optimally utilized as a promotional media to strengthen Mandalika's positive image and attract more tourists. This study aims to analyze the role of tour guides in Mandalika as a tourism promotion media to increase the attractiveness of tourist destinations. This research method uses a qualitative method with a SWOT analysis approach where researchers conduct in-depth interviews with tour guides in Mandalika and dig deeper into the promotional strategies carried out by Mandalika tour guides. The results of this study are expected to provide recommendations for the development of tour guide professionalism and contribute to a quality tourism industry.